Perbandingan Model Pendidikan Inklusi di Daerah Pedesaan dan Perkotaan: Okay, I can help you with that. Here is the English translation of the manuscript: Comparison of Inclusive Education Models in Rural and Urban Areas - Salsabila, Syifa Septiani; Rachman, Ichsan Fauzi (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Inclusive education is an educational service that includes all learners without exception, including children with special needs (CSN), to ensure equal access to education. This study aims to analyze and compare the implementation models of inclusive education in urban and rural areas in Indonesia, as well as to identify the challenges and solutions that emerge in both areas. The method used in this research is a Systematic Literature Review (SLR), by analyzing six national scientific articles retrieved from the Google Scholar database. The findings indicate that the challenges of inclusive education in both regions are fundamentally similar, namely the lack of Special Guidance Teachers (SGT), minimal training for teachers, and limited facilities and infrastructure. However, obstacles in urban areas are more related to policy coordination and technical implementation, while in rural areas, they are more focused on the limitations of human resources and infrastructure. Therefore, continuous teacher training, collaboration between schools, parents, and the community, as well as policy support from local governments are needed so that inclusive education can be realized equally and effectively throughout Indonesia.